Knitted nursery rhymes : recreate the traditional tales with knitted toys - Keen, Sarah, (Sarah Grace) (Lewes, East Sussex : The Guild of Master Craftsman Publications, 2013)
Provides instructions on knitting nursery rhyme character figurines, from Little Boy Blue and Humpty Dumpty to Little Miss Muffet and the cat with a fiddle.
Includes index.
Keywords: Knitting; Soft toy making; Knitting; Soft toy making; Nursery rhymes